Power Systems & Smart Energies - Derbel, Faouzi; Derbel, Nabil; Kanoun, Olfa (De Gruyter, 2020)
The book presents selected, extended and peer reviewed papers from the International Multiconference on System, Automation and Control held Leipzig in 2016. These are complemented with solicited contributions by international experts. This volume is devoted to power electronics in renewable energy systems as well as to hybrid renewable energy systems.
Keywords: elektronické knihy; electronic books